Myasthenia Gravis and pregnancy - Georgina Burke (Advances in Clinical Neuroscience & Rehabilitation, 2024)
Myasthenia Gravis (MG) is an acquired, autoimmune disorder of the neuromuscular junction, resulting in fluctuating skeletal muscle weakness and fatigue. MG prevalence increases with advancing age and is estimated to be 12 per 100 000 in European females below age 50 years [1]. The interplay of MG and pregnancy poses unique challenges for pregnant women and healthcare providers. In the UK, managing MG during pregnancy involves a multidisciplinary approach, bringing together neurologists, obstetricians, anaesthetists, and neonatologists. This collaboration is critical given that about 30% to 40% of women with MG may experience a worsening of their symptoms during pregnancy [2]. This review seeks to highlight the current consensus-based practice in the UK regarding MG management in pregnancy.